PENGARUH PRODUK WISATA, CITRA DESTINASI, KUALITAS PELAYANAN DAN WORD OF MOUTH TERHADAP KEPUTUSAN BERKUNJUNG PADA PANTAI BABANG DI KABUPATEN SIMEULUE - Tia Riska Ayunda; Rusydi Abubakar; Sapna Biby; Chalirafi Chalirafi (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
This study aims to analyze the influence of tourism products, destination image, service quality, and word of mouth on tourists’ visiting decisions to Babang Beach, Simeulue Regency. The research employed a quantitative approach by distributing questionnaires to 100 respondents and analyzing the data using multiple linear regression. The results show that all four variables have a significant effect, both simultaneously and partially, with a coefficient of determination (R²) of 0.634. Service quality emerged as the dominant factor with a regression coefficient of 0.306 and a significance value of 0.001. These findings indicate that improving service quality, strengthening destination image, developing tourism products, and enhancing word of mouth are crucial in encouraging tourists’ visiting decisions to Babang Beach.